Pengaruh Customer Review, Celebrity Endorser, Brand Image Terhadap Keputusan Pembelian Produk Thirft (Studi Kasus Konsumen Pada Imarket.id) - Aulia Rizka May Rosa; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purposes of this study are: 1) To determine and analyze the influence of customer reviews, celebrity endorsements, brand image on consumer purchasing decisions for thirft products at imarket.id, 2) To determine and analyze the influence of customer reviews on thirft product purchase decisions on consumers at imarket id, 3) To find out and analyze the influence of celebrity endorsement on consumer purchasing decisions for thirft products at imarket.id, 4) To determine and analyze the effect of brand image on consumer purchasing decisions for thirft products at imarket. This study uses an explanatory research type using a quantitative approach. The population and sample in this study were 60 iPhone consumers at iMarket.id. In this study, the information collection technique used was in the form of a questionnaire. The results showed that the variable customer review, celebrity endorsement, brand image had a significant effect on the purchasing decision variable of 0.000 < 0.05. Customer reviews have a significant effect on purchasing decisions of 0.020 < 0.05. Celebrity endorse has no significant effect on purchasing decisions of 0.167 < 0.05. Brand image has a significant effect on purchasing decisions of 0.003 < 0.05. Keywords: Customer Review, Celebrity Endorser, Brand Image and Purchase Decision